Rights Protection Regime for Internally Displaced Women and Children: Towards the Formation of A Metaframework - Bandyopadhyay, Rathin; Das, Chandrani (Kathmandu School of Law Review, 2013)
In the contemporary world, defining development has been a quagmire. This paper is an effort towards understanding the dilemma of internally displaced women and children, the questions of rehabilitation, resettlement, and reparation, while in the proces s, trying to draw useful and legitimate distinctions between the economic and social rights of internally displaced women and children due to communal violence, large scale projects, and natural disaster. The study is focused on the larger issues involved in development projects, making a comparative cost benefit analysis of the development on the social and individual welfare and the long term impact thereon. The paper envisages an insight to the projects, specifically on the physical forms of development, i.e. projects which require land expropriation and call for displacement by decree. Noticeably, such catastrophic development projects cause upheaval and displacement of communities. The paper scrutinizes such projects, including Dams, Industrialization, Mining (natural resource extraction), distributive policies, and other mega infrastructural projects, besides the lop-sided Disaster Management and reconstruction programs that cause misery to the masses in case of Natural disaster, looking on to the greater policy issues related to displacement, rehabilitation and the consequences thereof, especially on the women and children.